INTERTEKSTUALITAS JAKARTA SEBAGAI RUANG URBAN DALAM ANTOLOGI ESAI TIADA OJEK DI PARIS - Tjahjani, Joesana (Universitas Pendidikan Indonesia, 2020)
As a metropolitan city, Jakarta is growing rapidly both physically and demographically. Jakarta's socio-economic dynamics also show significant developments over time. In an essay titled Tiada Ojek di Paris, Seno Gumira Ajidarma discusses Jakarta as an urban space that is filled with modern human problems. This paper aims to show the intertextuality that exists in the collection of essays, as well as the intertextuality resulting from the mention of various other texts in the work. Lucien Goldmann's genetic structuralism approach, Julia Kristeva's intertextuality theory, and the concept of the production of space from Henri Lefebvre are used as analytical frameworks. Analysis of the text structure shows the identification of Jakarta as a problematic urban space and close to everyday life reality. This was told by the narrator as well as the focalizer from an academic perspective, according to the background of the author who is a writer as well as an academic. The intertextual relations that are built from a series of texts that exist in Tiada Ojek di Paris represent the reflection, criticism, and dominant discourse that produces social spaces in urban Jakarta. Meanwhile, the intertextuality that results from the mention of various other texts in the anthology of essays confirms the position of the writer as a writer and academic in constructing arguments.